Literatur Review :Kepatuhan Minum Tablet Fe dengan Kejadian Anemia pada Remaja - Eva Putrianingsih; Hapsari Windayanti, S.Si.T.; Lailatul Farihah; Lilis Suryani; Diana Rosanti; Annisa (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Adolescence is a period when individuals experience development by showing secondary sexual signs until they reach sexual maturity in the age range of 10-19 years (WHO, 2018). Low adherence and increased anemia in adolescents are problems that need to be addressed immediately, considering that young women are prospective mothers who will become pregnant and produce offspring for one generation. Based on the research carried out by the researchers, a review of the literature regarding adherence to taking FE tablets with anemia in adolescents still lacks adherence in consuming ef tablets so that there are still many adolescents who experience them. So this literature review was carried out aiming to determine adherence to drinking FE tablets with the incidence of anemia in adolescents. The research method used is literature review, namely by looking for theoretical references that are relevant to the case or topic. Article searches were carried out through Google Scholar and Garuda by checking the index through SINTA, Garuda, PKP and Google Scholar. Using the keyword 'Compliance with Taking Blood Supplement Tablets with Anemia in Adolescents'. The articles used have years of publication between 2015-2022. The results showed that there was a relationship between adherence to consumption of Fe tablets and anemia status p=0.0005 (p<0.05). The dominant variable multivariate result is adherence to consumption of Fe tablets with an opportunity of 61.555 times. The incidence of anemia in adolescents, especially young women adherence to taking Fe tablets. Abstrak Masa remaja merupakan masa dimana individu mengalami perkembangan dengan menunjukkan tanda-tanda seksual sekunder hingga mencapai kematangan seksual pada rentang usia 10-19 tahun (WHO, 2018). Rendahnya kepatuhan dan meningkatnya anemia pada remaja merupakan masalah yang perlu segera diatasi, mengingat remaja putri merupakan calon ibu yang akan hamil dan menghasilkan keturunan selama satu generasi. Berdasarkan penelusuran yang dilakukan peneliti, tinjauan literatur mengenai kepatuhan minum tablet FE dengan anemia pada remaja masih kurangnya kepatuhan dalam mengkonsumsi tablet ef sehingga masih banyak remaja yang mengalaminya. Maka kajian pustaka ini dilakukan bertujuan untuk mengetahui kepatuhan minum tablet FE dengan kejadian anemia pada remaja. Metode penelitian yang digunakan adalah literature review, yaitu dengan mencari referensi teori yang relevan dengan kasus atau topik. Penelusuran artikel dilakukan melalui Google Scholar dan Garuda dengan melakukan pengecekan indeks melalui SINTA, Garuda, PKP dan Google Scholar. Menggunakan kata kunci 'Kepatuhan Mengonsumsi Tablet Suplemen Darah dengan Anemia pada Remaja'. Artikel yang digunakan memiliki tahun terbit antara 2015-2022. Hasil analisis sejumlah 10 artikel didapatkan bahwa kepatuhan tablet Fe berhubungan dengan status gizi.Kejadian anemia pada remaja khususnya remaja putri dapat disebabkan oleh kepatuhan minum tablet Fe.